2017
DOI: 10.21037/mhealth.2017.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of CycleTel Family Advice: an SMS-based service to provide family planning and fertility awareness information in India

Abstract: Background: CycleTel Family Advice (CFA), an SMS-based service designed to improve knowledge of fertility and family planning (FP), was delivered to over 100,000 people in India from April to August 2015.The goal of CFA was to increase knowledge on a range of reproductive health topics, e.g., the menstrual cycle, fertility, and FP, and to increase positive perceptions and use of FP. This paper focuses on the best practices and operational challenges for providing an SMS service based on the implementation expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The majority of mHealth studies in sub-Saharan Africa have used SMS messages for health education, reminder messaging, and data collection; however, these strategies may have minimal effectiveness if they are not well integrated into existing healthcare systems or paired with other health provider and systems-based technologies such as providerfacing mHealth tools or patient-facing smart phone applications (25,30). Although patient-facing phone and tablet applications for fertility tracking exist worldwide, studies have shown low uptake of these tools in settings with low knowledge about fertility indicators and where women report skepticism of the applications' ability to correctly predict ovulation cycles (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of mHealth studies in sub-Saharan Africa have used SMS messages for health education, reminder messaging, and data collection; however, these strategies may have minimal effectiveness if they are not well integrated into existing healthcare systems or paired with other health provider and systems-based technologies such as providerfacing mHealth tools or patient-facing smart phone applications (25,30). Although patient-facing phone and tablet applications for fertility tracking exist worldwide, studies have shown low uptake of these tools in settings with low knowledge about fertility indicators and where women report skepticism of the applications' ability to correctly predict ovulation cycles (47).…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, several studies have demonstrated the acceptability, feasibility, and effectiveness of SMS messages aimed at increasing rates of HIV testing (18) and ART adherence (19)(20)(21), improving sexual behavior measurement (22,23), and increasing healthcare worker adherence to HIV treatment guidelines (24). mHealth interventions have also been used to deliver information regarding menstrual cycle timing and family planning methods to address health systems challenges related to service availability and efficiency during clinic visits (25)(26)(27)(28)(29). However, these mHealth programs are primarily directed at patients rather than healthcare providers, and none have been developed to specifically support safer conception among HIV serodiscordant couples (30).…”
Section: Introductionmentioning
confidence: 99%
“…Although 2 apps have received clearance from the United States Food and Drug Administration for use as a contraceptive method (Natural Cycles in 2018, 22 which also received CE Marking in Europe, and Clue in 2021 23 ), most such apps or devices are not tested or indicated for this purpose and may offer predictions of unknown accuracy regarding the timing of fertile days. 24,25 Research focused specifically on FABM use in low-and middle-income countries (LMICs) has been particularly limited (with exceptions from the United States Agency for International Development and the Institute for Reproductive Health at Georgetown University 18,[26][27][28][29][30][31] ). However, there are existing and emerging reasons for greater understanding around FABM use in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…SDM is recognized as a modern method of family planning by the United States Agency for International Development (USAID) (4) and the World Health Organization (5), and has an efficacy rate of 95% with perfect use and 88% for typical use, similar to other userinitiated methods (6). Extensive studies have been conducted on the SDM with the physical CycleBeads product, and it has been found to be a low-cost, highly acceptable family planning method (6,7). Research on the initial use and acceptability of the CycleBeads app as a digital platform for using SDM in Kenya found that the app was understood and used correctly by women who downloaded it, and social media (specifically Facebook advertising) was found to be a low-cost way of reaching potential users (7).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted on the SDM with the physical CycleBeads product, and it has been found to be a low-cost, highly acceptable family planning method (6,7). Research on the initial use and acceptability of the CycleBeads app as a digital platform for using SDM in Kenya found that the app was understood and used correctly by women who downloaded it, and social media (specifically Facebook advertising) was found to be a low-cost way of reaching potential users (7).…”
Section: Introductionmentioning
confidence: 99%